A ready-made life : early masters of modern Korean fiction - Kim, Chong-un, 1929-; Fulton, Bruce (University of Hawai'i Press, 1998)
A Ready Made Life is the first volume of early modern Korean fiction to appear in English in the U.S. Written between 1921 and 1943, the sixteen stories are an excellent introduction to the riches of modern Korean fiction. They reveal a variety of settings, voices, styles, and thematic concerns, and the best of them, masterpieces written mainly in the mid-1930s, display an impressive artistic maturity. Included among these authors are Hwang Sun-won, modern Korea's greatest short story writer; Kim Tong-in, regarded by many as the author who best captures the essence of the Korean identity; Ch'ae Man-shik, a master of irony; Yi Sang, a prominent modernist; Kim Yu-jong, whose stories are marked by a unique blend of earthy humor and compassion; Yi Kwang-su and Kim Tong-ni, modernizers of the language of twentieth-century Korean fiction; and Yi Ki-yúng, Yi T'ae-jun, and Pak T'ae-won, three writers who migrated to North Korea shortly after Liberation in 1945 and whose works were subsequently banned in South Korea until democratization in the late 1980s. One way of reading the stories, all of which were written during the Japanese occupation, is that beneath their often oppressive and gloomy surface lies an anticolonial subtext. They can also be read as a collective record of a people whose life choices were severely restricted, not just by colonization, but by education (either too little or too much, as the title story shows) and by a highly structured society that had little tolerance for those who overstepped its boundaries. Life was unremittingly onerous for many Koreans during this period, whatever their social background. In the stories, educated city folk fare little better than farmers and laborers. A Ready-Made Life will provide scholars and students with crucial access to the literature of Korea's colonial period. A generous opening essay discusses the collection in the context of modern Korean literary history, and short introductions precede each story. Here is a richly diverse testament to a modern literature that is poised to assume a long overdue place in world literature.